IBN Ḥazm and Midrash - Mazuz, Haggai (Journal of Semitic studies, 2017)
‘Alī b. Aḥmad b. Ḥazm devoted much of his oeuvre to polemics against Jews and Judaism. In so doing, he often based his case on what he said were Jewish sources — which, he insisted, the Jews had falsified and fabricated. How familiar was he with these sources, and how did he acquire this familiarity? the article investigates a series of references to Jewish sources by Ibn Ḥazm, attempts to determine their origin — possibly the Talmuds and other post-Biblical works that contain Midrash — analyses his treatment of them, and ventures several hypotheses about the roots of his familiarity. While scholarship to date provides no unequivocal proof of the correctness of these hypotheses, Ibn Ḥazm's recourse to Jewish sources in his polemical writings is evidently the result of thorough research on his part.